Pteryxin enhances human NK-cell cytotoxicity by upregulating NKp30, NKp46, and 2B4 via ERK/AKT signaling - Park, Eun Sun; Kim, Jong-Tae; Hwang, Yo-Sep; Han, Jahyeong; Park, Hyo-Min; Yoon, Hyang Ran; Cho, Hee Jun; Lee, Hee Gu (Frontiers in Pharmacology, 2026)
Natural killer (NK) cells play critical roles as effector cells by directly identifying and killing virus-infected and cancer cells. Pteryxin exhibits diverse antioxidant and anti-inflammatory effects; despite its known properties, the influence of pteryxin on NK cells is not understood fully. In this study, we evaluated the potential of pteryxin to enhance the cytotoxicity of NK cells. Pteryxin markedly enhanced the cytotoxic activities of both NK-92 and primary human NK cells against leukemia and colorectal cancer cell lines in a dose-dependent manner. Furthermore, it elevated the surface expression of key activating receptors NKp30, NKp46, and 2B4 in the NK-92 cells. This upregulation was accompanied by activation of the ERK and AKT signaling pathways, leading to increased production of cytotoxic mediators, including granzyme B and perforin. Moreover, in vivo studies using the CT26 mouse model revealed that pteryxin administration inhibited tumor growth in a dose-dependent manner. NK cells from the pteryxin-treated mice demonstrated enhanced cytotoxicity against YAC-1 leukemia cells. The anticancer effects of pteryxin were abolished when the NK cells were significantly reduced using anti-asGM1 antibody, confirming the critical role of the NK cells in its antitumor activity. Collectively, these findings demonstrate that pteryxin stimulates the ERK and AKT signaling pathways to enhance NK cell cytotoxicity against tumors, supporting its potential as a novel enhancer of NK-cell-driven antitumor responses.